All-region-applicable, continuous power supply of graphene oxide composite. Issue 6 (22nd May 2019) - Huang, Yaxin; Cheng, Huhu; Yang, Ce; Yao, Houze; Li, Chun; Qu, Liangti
Abstract : This study demonstrates an all-region-applicable moist-electric generator (MEG) based on a highly hydrophilic graphene oxide composite, delivering considerable electric energy over a wide temperature (−25 °C to 50 °C) and relative humidity range (RH, 5–95%). Abstract : Green energy has gained growing interest due to the increasing serious environmental pollution and energy crisis. Herein, we developed an all-region-applicable moist-electric generator (MEG) based on a graphene oxide composite to harvest energy from atmospheric moisture over a wide range of temperature (−25 °C to 50 °C) and relative humidity (RH, 5–95%). It could continuously deliver a comparatively high open-circuit voltage of ∼0.6 V for more than 120 hours under an ambient environment with a small device size of only about 0.1 cm −2 . The electric output could be enhanced to directly power many commercial electronic devices without the need for external rectifying circuits and capacitors. The experiments and simulations suggest that the spontaneous absorption of water molecules and the directional migration of ions within the composite mainly contribute to the electricity generation. This study provides new insights for the generation of sustained green energy from atmospheric moisture in arbitrary ambient environments, holding immense promise for widespread practical applications in complex environments.